2023
DOI: 10.1039/d3cp02043f
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating two-dimensional magnetic states via electric field and pressure

Abstract: Topological spin configurations have been an intriguing topic due to the exotic transport properties and promising applications in spintronic devices. The discovery of two-dimensional (2D) magnetic materials such as CrI3...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…To address these challenges, innovative strategies are imperative prompting the exploration of multiferroic memory systems [18][19][20][21][22] that integrate 2D FE with carefully selected FM components. The multiferroic memory, with an atomic thickness, preserves the advantageous characteristics of both components [23][24][25][26][27]. The discernible electric or optical signals inherent in the system's dual states play a pivotal role in facilitating data extraction, showcasing its superiority in the data reading process.…”
Section: Introductionmentioning
confidence: 99%
“…To address these challenges, innovative strategies are imperative prompting the exploration of multiferroic memory systems [18][19][20][21][22] that integrate 2D FE with carefully selected FM components. The multiferroic memory, with an atomic thickness, preserves the advantageous characteristics of both components [23][24][25][26][27]. The discernible electric or optical signals inherent in the system's dual states play a pivotal role in facilitating data extraction, showcasing its superiority in the data reading process.…”
Section: Introductionmentioning
confidence: 99%
“…The skyrmion state created at room temperature is particularly advantageous for studying their manipulation and exploring potential applications. The revelation of room-temperature ferromagnetic vdW materials, such as (Fe 1– x Co x ) 5 GeTe 2 , , presents an excellent opportunity for creating room-temperature skyrmions. Additionally, recent studies have demonstrated that Fe 3 GaTe 2 exhibits ferromagnetism and topological Hall effects at room temperature, , suggesting its potential to host room-temperature skyrmions.…”
mentioning
confidence: 99%